2011
DOI: 10.1590/s0103-84782011005000019
|View full text |Cite
|
Sign up to set email alerts
|

Silagem de grão úmido de milho na alimentação de coelhos em crescimento

Abstract: RESUMO Dois experimentos foram realizados para determinar o valor nutritivo da silagem de grãos úmidos de milho (SGUM) e avaliar os efeitos da substituição gradativa do milho seco das rações pela ABSTRACT Digestibility and performance experiments were carried out to evaluate the nutrients digestibility coefficients of high moisture corn silage (HMCS) and the gradative replacing (0, 25, 50, 75 and 100%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
1
0
3
Order By: Relevance
“…The improvement in body weights, BWG, and ADG and the worseness in the feed to gain ratios after supplementation with organic acids (formic acid) has been seen in this study are in agreement with those reported previously (33,34). The first authors found feed intake to decrease and consequently, improvement feed conversion with the supplementation of diet with citric acid from 0.5% and up to 2.0% whereas, the second author recorded improvement of body weight gains with 0.5% fumeric, citric, and malic acids.…”
Section: Discussionsupporting
confidence: 94%
“…The improvement in body weights, BWG, and ADG and the worseness in the feed to gain ratios after supplementation with organic acids (formic acid) has been seen in this study are in agreement with those reported previously (33,34). The first authors found feed intake to decrease and consequently, improvement feed conversion with the supplementation of diet with citric acid from 0.5% and up to 2.0% whereas, the second author recorded improvement of body weight gains with 0.5% fumeric, citric, and malic acids.…”
Section: Discussionsupporting
confidence: 94%
“…Maertens; Berchiche (2016) e Scapinello et al (2011) apresentaram nos seus trabalhos consumos médios diários sem especificar o consumo de silagem provavelmente porque não ofereceram silagem à vontade aos animais ou não controlaram o consumo de silagem em separado.…”
Section: Raçãounclassified
“…A silagem é a forragem conservada pelo processo de fermentação anaeróbica e segundo Teixeira, Amin e Mello (2009), o milho é a espécie forrageira mais utilizada para ensilagem devido à sua boa qualidade nutricional, aceitação pelos animais e produção de massa seca por hectare. A silagem de grão úmido de milho (SCAPINELLO et al, 2011), a silagem de milho de planta inteira (GUERMAH;MAERTENS;BERCHICHE et al 2016) e a planta inteira de milho desidratada (MARTÍNEZ et al, 2006) foram eficazes na alimentação de coelhos em crescimento, porém continuam necessários mais estudos para maximizar a inclusão na alimentação dos animais. O girassol também pode ser ensilado e utilizado na dieta animal, porém ainda são escassas as informações da utilização de girassol na dieta de coelhos.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Studies related to animal feed have discussed the care needed to ensure the quality and safety of the product (SANTIN, 2006), evaluate the losses (the quantity, costs and contaminations of the products) caused by the equipment maintenance in different stages of a feed production mill (CORADI et al, 2015). Predominately there are also studies related to diet formulation for different animals (SCAPINELLO et al, 2011;ZANGERONIMO et al, 2009). However, up to now, few studies were focused on workplace safety conditions for the workers, in units of animal feed mills (CARVALHO et al, 2008;SILVA et al, 2011).…”
Section: Introductionmentioning
confidence: 99%